2012
DOI: 10.1097/der.0b013e31823d180f
|View full text |Cite
|
Sign up to set email alerts
|

Fragrance Series Testing in Eyelid Dermatitis

Abstract: Our results suggest that there may be a significant benefit to fragrance series testing in patients with eyelid dermatitis. Fragrance tray inclusion in this population may identify additional cases of fragrance allergy that are missed by the standard series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
2
4
1
Order By: Relevance
“…This can be explained as in majority of our patients facial creams were suspected as offending agents. In our present study colophony was positive in 4.61% patients, which was in accordance with results obtained by Amin et al, (2) (4.3%), Cooper et al, (14) (3%), while Goosens et al, (11) found colophony to be positive in 7.29% and Kurt et al, (16) in 7%. The higher positivity may be due to a very large sample size in their studies.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This can be explained as in majority of our patients facial creams were suspected as offending agents. In our present study colophony was positive in 4.61% patients, which was in accordance with results obtained by Amin et al, (2) (4.3%), Cooper et al, (14) (3%), while Goosens et al, (11) found colophony to be positive in 7.29% and Kurt et al, (16) in 7%. The higher positivity may be due to a very large sample size in their studies.…”
Section: Discussionsupporting
confidence: 83%
“…Fragrance mix was positive in 10.77% of patients in our study. Similar results were found by Feser et al, (16) in 11.5%, Goosens et al, (11) in 15.46% and Herro et al, (15) in 19.35%, while Valesschi et al, (7) in 8%, Reitshel et al, (12) in 7.1% and Cooper et al, (14) in 6% of…”
supporting
confidence: 79%
See 1 more Smart Citation
“…70 In seven studies in which patients with eyelid dermatitis or periorbital dermatitis were patch tested with MP, frequencies of sensitization ranged from 1.7% to 17%, but in five of the seven studies, the frequency was <7%. [72][73][74][75][76][77][78] In three investigations in which relevance was addressed, rates of relevant reactions were 43%, 77 58%, 78 and 75%, 74 but the culprit products were not mentioned. In four studies with a control group, the frequency of sensitization to MP was significantly lower than in routine testing.…”
Section: Relevance and Causative Productsmentioning
confidence: 99%
“…Table 2 summarizes Among the fragrance allergens commonly implicated in ACD, fragrance mix I and mix II (Chemotechnique Diagnostics) have elicited an allergic response in 9.6 and 6 % of the general population, respectively [55]. Despite this response rate, Wenk et al found 36 % of their study population of patients with eyelid dermatitis to test positive for allergens in their supplemental fragrance series, even after a negative reaction to fragrances in the standard series [44]. Thus, the use of both the standard patch-testing series and a fragrance tray may be beneficial in determining the cause of ACD (Table 3).…”
Section: Patch Testingmentioning
confidence: 99%